2013
DOI: 10.1002/pola.26716
|View full text |Cite
|
Sign up to set email alerts
|

Well‐defined thermoresponsive dendritic polyamide/poly(N‐vinylcaprolactam) block copolymers

Abstract: The first‐ and second‐generation well‐defined thermoresponsive amphiphilic linear–dendritic diblock copolymers based on hydrophilic linear poly(N‐vinylcaprolactam) and hydrophobic dendritic aromatic polyamide have been synthesized via reversible addition fragmentation chain transfer polymerization of N‐vinylcaprolactam by employing dendritic chain‐transfer agents possessing a single dithiocarbamate moiety at the focal point. These linear–dendritic copolymers exhibit reversible temperature‐dependent phase trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
(77 reference statements)
1
18
0
Order By: Relevance
“…Only a few CRP techniques can properly mediate the radical polymerization of NVCL, including reversible additionfragmentation chain transfer (RAFT) [16][17][18][19][88][89][90][91][92][93][94][95], a combination of ring-opening polymerization (ROP) and RAFT [96,97], atom transfer radical polymerization (ATRP) [98], and Cobalt mediated radical polymerization (CMRP) [20,29,66]. Devasia et al [88] reported the first sequential RAFT polymerization to prepare block copolymers of A c c e p t e d M a n u s c r i p t 25 polymerization.…”
Section: Block Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few CRP techniques can properly mediate the radical polymerization of NVCL, including reversible additionfragmentation chain transfer (RAFT) [16][17][18][19][88][89][90][91][92][93][94][95], a combination of ring-opening polymerization (ROP) and RAFT [96,97], atom transfer radical polymerization (ATRP) [98], and Cobalt mediated radical polymerization (CMRP) [20,29,66]. Devasia et al [88] reported the first sequential RAFT polymerization to prepare block copolymers of A c c e p t e d M a n u s c r i p t 25 polymerization.…”
Section: Block Copolymersmentioning
confidence: 99%
“…al [93]. synthesized first and second-generation well-defined linear-dendritic block copolymers containing PNVCL linear chains and polyamide dendrons via RAFT polymerization of NVCL using dendritic CTA´s possessing a single dithiocarbamate moiety.…”
mentioning
confidence: 99%
“…As an alternative thermosensitive block, Bi et al have investigated poly( N ‐vinylcaprolactam) (PNVCL), which was polymerized from the focal point of G1 and G2 polyamide (PA) dendrons via RAFT . The degree of polymerization of PNVCL was 46 and 55 for the G1 and G2 systems, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding diblock copolymer analogues were prepared using monodendron chain‐transfer agent to polymerize NIPAM as well as pyrene‐labelled NIPAM . A copolymer of dendritic aromatic polyamide as hydrophobic block and poly( N ‐vinyl caprolactam) as hydrophilic block was also synthesized using RAFT . Although reversible transition between micellar assembly and disassembly with temperature has been reported in linear–dendritic copolymers, there are few reports that describe temperature‐responsive transformation of one well‐defined morphology into another.…”
Section: Introductionmentioning
confidence: 99%
“…A copolymer of dendritic aromatic polyamide as hydrophobic block and poly( N ‐vinyl caprolactam) as hydrophilic block was also synthesized using RAFT . Although reversible transition between micellar assembly and disassembly with temperature has been reported in linear–dendritic copolymers, there are few reports that describe temperature‐responsive transformation of one well‐defined morphology into another. For example, poly(benzyl ether) dendron‐ block ‐PNIPAM copolymer synthesized using a dendron atom transfer radical polymerization (ATRP) macroinitiator exhibited a change in morphology from micelles to entangled nanotubes above the LCST .…”
Section: Introductionmentioning
confidence: 99%